Conformal inflation with chameleon coupling - Bernardo, Heliudson [UNESP]; Costa, Renato; Nastase, Horatiu [UNESP]; Weltman, Amanda (IOP Publishing, 2019)
We investigate the possibility that the inflaton, in particular in conformal inflation models, is also a chameleon, i.e. that it couples to the energy density of some heavy non-relativistic matter present during inflation. We find new and interesting attractor-like behaviours, either prolonging inflation, or changing the observables ns,r, depending on the sign of the chameleon coupling exponent. We also check that the chameleon coupling with the heavy matter field strongly suppresses entropy modes during inflation.
Keywords: cosmology of theories beyond the SM; ination; physics of the early universe